Effects of chromium powder mixed in electrical discharge machining of AISI D2 hardened steels - Idris, Muhammad Ridzuan (2015)
Nowadays, electrical discharge machining (EDM) is the non-conventional method that has been used extensively in machining hard material that is commonly used in mold and die industry but the limitations of EDM will cause lower productivity and poor surface quality. EDM becomes most apparent by using powder metallurgy electrode together with chromium (Cr) powder suspension into the dielectric fluid which has led to the increasing of productivity and good quality performance and characteristics. Therefore, by combining of both EDM parameters and machining conditions by incorporating with specific magnetic system plus integrated with existing filter system, it is highly expected that the machining speed can be enhanced. However, there are difficulties to determine the best combination of these machining parameters in order to increase the material removal rate (MRR) and at the same time to reduce the electrode wear rate (EWR) with the acceptable surface integrity. This research emphasizes the studies of Cr powder mixed in EDM machining of AISI D2 hardened steel using copper tungsten electrode which has been done successfully. Data were analysed using design of three factors at a time consisted of peak current (Ip), pulse-on (Pon) and powder concentration(C). Discussions were made on the responses such as MRR, EWR, Surface Roughness (Ra), surface morphology, recast layer (RL) and microhardness (MH) on the selected samples from the same machining conditions. Results have proved that Ip was the most significant parameter which has influenced the machining responses on Cr powder mixed EDM of AISI D2. It is also found that proper powder concentration of 2gram/litre enhanced the machining efficiency particularly in MRR. Furthermore, introduction of proper addition of Cr powder in the dielectric also decreased Ra and RL thickness. The EWR increased as the peak current increased, but inversely with pulse-on. In general, the possibility of EDM process for machining AISI D2 tool steel by incorporating Cr powder mixed in the dielectric is acceptable and the entire objectives were successfully proven.